Consumer preference in regard of electromobility - Comparison between Czech Republic and Germany - Hünefeld, Lukas (2019)
This study deals with the relationship between macro-economic factors and the preference of customers regarding electromobility. By comparing the market envrionment of the Czech Republic and Germany, this thesis aims to identify factors that positively influence an introduction of electric cars for the general public. For that reason a survey has been conducted, which compares the openness/readiness of customers in the Czech Republic and Germany conceding the topic, and whether the observed differences can be linked to the market environment.